Allogeneic hematopoietic stem cell transplant recipients in Spain: Human leukocyte antigen characteristics and diversity by high‐resolution analysis. (17th January 2021) - Guerreiro, Manuel; Planelles, Dolores; Aguilar‐Gallardo, Cristóbal; Lorenzo, José Ignacio; Montoro, Juan; Sanz, Jaime; Balaguer, Aitana; Gómez, Inés; Solves, Pilar; Pérez, Ariadna; Blanquer, Miguel; Espigado, Ildefonso; et al.
Abstract : There are many studies on the polymorphism of the HLA system in healthy donor populations, such as registries of unrelated bone marrow donors. Investigations on the characterization of the HLA complex in hematopoietic stem cell transplant (HSCT) patients, however, are scarce, at least in the Spanish population. This study presents a large‐scale analysis of allelic diversity and HLA distribution at a high‐resolution level in 2886 patients undergoing HSCT in Spanish centres of the " Grupo Español de Trasplante Hematopoyético y Terapia Celular " during a period of 11 years. Allelic diversity analysis identified 67 HLA‐A, 133 HLA‐B, 60 HLA‐C, 63 HLA‐DRB1, 24 HLA‐DQB1 and 27 HLA‐DPB1 different alleles. Rare alleles were detected among which 33 alleles had not been reported in the European catalog of common and well‐documented HLA alleles. Regarding the distribution of five genes‐haplotypes, it was observed that the five most frequent extended haplotypes found in our population were between the most common in other Spanish populations, both in patients and in healthy subjects. However, some particular haplotypes were also detected. Bilocus associations HLA‐C ~ B and ‐DRB1 ~ DQB1 were analyzed in order to predict the probability of finding 10/10 matched donors in registries. We found HLA‐B alleles showing a great diversity of combinations with HLA‐C alleles and unusual associations involving a negative predicting factor. In the field of adoptive therapies, our work supports the necessity to expand further research of TCR‐engineered cells, adoptive transfer of virus‐specific T‐cells and vaccines to target HLA alleles other than A*02:01 . HLA alleles such as A*01:01, A*03:01, A*24:02, B*44:03, B*07:02 or B*51:01, might be considered new targets due to its high frequency in our population.